PENGELOLAAN PEMBELAJARAN HYBRID LEARNING DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI SMAN 13 BONE - Eka Lestari, Sonia; Susi, Susi; Aswin, Aswin; Astuti, Astuti (DIDAKTIKA, 2022)
Online learning emerged as a form of learning pattern in the information technology era as it is today. Hybrid learning as a learning model in which there is a combination of face-to-face learning in the classroom and coupled with learning using computers both offline and online. Hybrid learning is an effort made to develop students' knowledge and skills to support their learning achievement. The purpose of this study is to describe how the planning, implementation and evaluation of hybrid learning lessons are carried out by teachers at SMAN 13 Bone. This research uses a qualitative approach with an exploratory case study method. This research was conducted at SMAN 13 Bone in the academic year 2022/2023. Data collection techniques used are interviews and observation. The results showed that the management of hybrid learning learning went well. This can be seen from 3 stages, including: (1) Planning: the teacher prepares the lesson plans and the platform used. (2) Implementation: the teacher divides several sessions and carries out learning according to the lesson plan. (3) Evaluation: authentic assessment, self assessment, project assessment, and test.